An Unsuccessful Reform on the Local Public Contracts Law in Korea - Sundoo Hwang (KDI Journal of Economic Policy, 2021)
In Korea, local governments and local agencies had to apply a version of the first price auction augmented by an ex-post screening process when they procure construction contracts. However, this first price auction had been criticized because it was felt that too much price competition could lead to poor ex-post performance in construction. In response, the existing auction method was recently replaced by a version of the average price auction with a similar screening process. This paper empirically examines the effectiveness of this reform and finds that the replacement only increases the fiscal burden of local governmental bodies without making any improvement in the ex-post performance.
Keywords: D44; H57; K12; 330; Local Government; Procurement; Average Price Auction; Screening; Price Competition; Ex-Post Performance